A Text-Syntactic Approach to the Book of Exodus - Gyu-Sang Jin (구약논단, 2023)
Eep Talstra established the text-linguistics based on the foundation put by Harald Weinrich and Wolfgang Schneider. It seeks to observe all the linguistic features and annotations in a text and judges the relationship between two clauses, whether hierarchical or otherwise parallel. It recursively goes through the relationship between all the clauses in a text and discovers a syntactic-hierarchical structure of a text. The size of a text could be a unit from the smallest section through a paragraph, chapter, etc., to the largest unit, for example, a book like Exodus or even the Pentateuch or a bigger textual unit. This paper starts from the research question of the function of EDSF (Elaborate Divine Speech Formula: YHWH spoke to Moses + double locative + time phrase) in Num 1:1. To study it; the paper observes the verb form and its position in the clause as ETCBC approach pays attention to other constituents in a clause, and finds all the occurrences of EDSFs in the Pentateuch, and elaborates on the effect of the locative and temporal phrases in EDSF, and reaches the assumption that EDSFs (YHWH spoke to Moses + locative phrase or time phrase) might demarcate a larger textual unit at a higher textual level than BDSF does. The three EDSFs in Exodus split Exodus into three major divisions: 1:1-4:18, 4:19-11:10, and 12:1-40:38. This paper elaborates on how the three EDSFs are parallel and the textual outline of Exodus. Lastly, this paper will discuss the function of a textual unit with scholars' demarcations and argue the advantage of the demarcations in the syntactic-hierarchical structure and the demarcations. KCI Citation Count: 0